Faktor-faktor yang Memengaruhi Pendapatan Petani Kentang di Desa Ranupani, Kecamatan Senduro, Kabupaten Lumajang - Wilujeng, Resa Putri Tri; Ibrahim, Jabal arik (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Potato is a major crop that is the main source of income for farmers in Ranupani Village. In addition, the production costs required are also very high, including fertilizer, labor, pesticides and land tax. The purpose of this study is to identify the amount of income received by potato farmers in Ranupani area. In addition, the next objective is to analyze several factors that can influence the income of potato farming in Ranupani area. The method used is a quantitative approach with an explanatory research design using primary data. The study population was 155 farmers with simple random sampling method obtained a total sample of 35 farmers. The method to analyze the income is by reducing the total revenue (TR) with total cost (TC), while multiple linear regression analysis is done to analyze some factors that can influence the farm income. The results of the study obtained the income received by potato farmers in Ranupani Village Area reached a range of Rp. 35,321,857 which means that farmers have benefited from the potato farming. Then the results of the data that have been processed show that the independent variables or independent variables together significantly affect the dependent variable or the dependent variable, but partially only the variables of fertilizer costs and seed costs that influence the income of potato farming.